Damage Characteristic of Thermal Shock on the Physical and Dynamic Compressive Properties of Granite. (19th April 2022) - Shu, Ronghua; Huang, Lijinhong; Zhi, Xueyi; Han, Zhenyu; Lai, Yuzhang; Li, Huizhen; Wang, Chun
Abstract : Thermal shock is common in fire disaster and blasting of rock engineering; moreover, the rock mass bears dynamic mechanical disturbance frequently. In order to study the damage characteristics of thermal shock on physical and dynamic compressive properties, the thermal shock damage of granite treated to different temperatures at different heating rates was obtained by measure the ultrasonic wave velocity, and the internal structures were obtained by scanning electron microscopy experiments. By using split Hopkinson pressure bar, the dynamic experiments on granite treated to 400°C and 600°C at heating rates of 1, 2, 4, 6, 10, 20, 30, and 40°C/min were carried out. Thereby, the damage characteristics of thermal shock on the physical and dynamic compressive properties of granite were obtained. The results show that there is a heating rate threshold value between 6 and 10°C/min, which divides the thermal shock damage. Before the threshold value, the thermal shock does not appear. The dynamic compressive strength, dynamic elastic modulus, and density decrease; however, peak strain increases as the thermal shock damage increases. The researches of thermal effect on granite by heating with the heating rate below or equal to 6°C/min could avoid thermal shock. The research could provide a theoretical foundation for rock engineering suffered thermal shock, such as geothermal reservoir.